Hubungan Literasi Digital dengan Kesiapan Teknologi menggunakan TRI (Technology Readiness Index) pada Pengguna Rekam Medis Elektronik di Klinik Utama Grha Atma Bandung - Yosi Siti Nur Azizah; Tria Saras Pertiwi; Hosizah Hosizah; Mieke Nurmalasari (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
Digital transformation in healthcare encourages healthcare facilities to implement Electronic Medical Records (EMR). The success of EMR implementation is not only determined by system and infrastructure readiness but also influenced by users' digital literacy and technology readiness. This study aimed to analyze the relationship between digital literacy and technology readiness using the Technology Readiness Index (TRI) among EMR users at Grha Atma Primary Clinic Bandung. This study used a quantitative approach with a cross-sectional design. The sample consisted of 31 respondents using total sampling. Data were collected using a digital literacy questionnaire adapted from DHLI and a TRI questionnaire. Data analysis included univariate analysis (Three Box Method) and bivariate analysis using Spearman Rank correlation. The results showed that digital literacy was categorized as high across all dimensions. Technology readiness indicated that optimism and innovativeness were high, while discomfort and insecurity ranged from moderate. Spearman test results showed a significant positive relationship between digital literacy and technology readiness (p = 0.003; r = 0.519). This study concludes that digital literacy significantly influences technology readiness among EMR users. Improving digital literacy is essential to enhance technology readiness and optimize EMR implementation.